Quad-polarimetric ApRES measurements along a 6 km-long transect at the WAIS Divide, December 2019 ... - Young, Tun Jan; Dawson, Eliza (NERC EDS UK Polar Data Centre, 2021)
Polarimetric phase-sensitive radar measurements were collected at the Western Antarctic Ice Sheet (WAIS) Divide on the 25th and 26th December 2019. The measurements were conducted at 10 sites along a 6 km-long transect ~5-10 km northeast of the location of the WAIS Divide Deep Ice Core. At each site, a suite of four quadrature (quad-) polarimetric measurements were collected using an autonomous phase-sensitive radio echo sounder (ApRES) in a single-input single-output (SISO) configuration. The study is part of the Thwaites Interdisciplinary Margin Evolution (TIME) project of the International Thwaites Glacier Collaboration (ITGC), and is a collaboration between the United States National Science Foundation (NSF) and the United Kingdom Natural Environment Research Council (NERC). It was funded by UK Natural Environment Research Council (NERC) research grant NE/S006788/1 and USA National Science Foundation (NSF) research grant 1739027. ... : For each site, a suite of four quadrature (quad-) polarimetric measurements were collected using an autonomous phase-sensitive radio echo sounder (ApRES) in a single-input single-output configuration. Each measurement consisted of 100 chirps, with each chirp consisting of a linear sweep from 200 to 400 MHz over the course of 1 second, corresponding to a centre frequency of 300 MHz over a bandwidth of 200 MHz. For each measurement, two open-structure antennas (1 transmitting, 1 receiving) were positioned with their centres 8.00 m apart in combinations of four orthogonal antenna orientations, where antennas were positioned in either a horizontal (h) or vertical (v) alignment with respect to the antenna's electric plane. The four orientation combinations are therefore hh, hv, vv, and vh. Measurements were conducted sequentially, and each antenna pair orientation was established by rotating one or both antennas by 90° with respect to their previous orientations while keeping the position of each antenna centre ...